Electrical Resistivity and Mechanical Properties of Tungsten Carbide Reinforced Copper Alloy Composites: Experimental Investigation - Girish, B. M.; Basawaraj, B. R.; Satish, B. M.; Somashekar, D. R. (New Approaches in Engineering Research Vol. 15, 2021)
The electrical, mechanical, and physical properties of Cu-WC composites are described in this paper. Copper is widely used as a material for electrical contacts on account of its high electrical and thermal conductivities, low cost and ease of fabrication. By stirring molten alloy to obtain vortex using a steel stirrer covered with alumina and rotating at 500 rpm, composites of copper alloy containing 0–8 weight percent WC were manufactured utilising the liquid metallurgical approach. The experimental results demonstrated that as the WC content in the composites increases, the density of the composites increases, which is consistent with the values calculated using the mixtures rule. Cu–WC composites' hardness and ultimate tensile strength improved as the WC concentration in the matrix increased, while ductility decreased. For ultimate tensile strength and hardness, a model analysis of composites was performed, and it was discovered that the approximate mechanics of materials prediction Paul model is consistent with experimental results. The experimental values were consistent with the theoretical results of electrical resistivity of composites estimated using the P.G Klemens model.